A Confucian in Buddhist clothing? – Interpreting Nishida's conception of the good as a realisation of the Mandate of Heaven. Issue 4 (2nd October 2018) - Rhydwen, Thomas Parry
ABSTRACT: In this study, I examine the Confucian influence upon  An Inquiry into the Good, the first publication of Nishida Kitarō. Nishida's student Kōsaka Masaaki depicts his mentor's conception of the good in terms of realising the 'Mandate of Heaven'. Taking this to be indicative of the importance of Confucianism for Nishida's early thought, I compare his philosophy of pure experience and ethical project of 'self-realisation' with corresponding ideas found in the Confucian corpus. I especially focus on the  Great Learning  and  Doctrine of the Mean  as interpreted by the Neo-Confucian Wang Yang-Ming. This study builds upon the pioneering work of Michel Dalissier, Dermott Walsh and David Williams on the Kyoto School and Confucianism. My portrayal of Confucianism is indebted to the 'philosophical' translations of Roger Ames, David Hall and Henry Rosemont, Jr., which bring into relief the tradition's 'relational ontology' that Graham Parkes teaches is shared by the Kyoto School.